Does program linking with insurance makes agriculture insurance sustainable? - Timsina, Krishna P.; Ghimire, Yuga N.; Kandel, Ghanshyam; Devkota, Deepa (Journal of Agriculture and Natural Resources, 2018)
Agriculture insurance is most common forms of risk transfer in agriculture. It is often compulsory for borrowers of agricultural loans in low and middle income countries. This study tries to find out the status of compulsory agriculture insurance in Nepal and its sustainability through answering question “are compulsory agriculture insurance programs making agricultural insurance sustainable? Or we have to think differently for its sustainability. Household survey were conducted using pre-tested semi structured questionnaire in eight districts. Altogether 377 insurer farmers (132 crop and 245 livestock farmers) were selected from the list of target population using simple random sampling technique. Similarly, five cases were selected from the study districts. Result shows that Government of Nepal (GoN) has developed both cost of production and value based insurance products based on farmers demand. Basically, premium rate is fixed as five percent to cost of production based and seven percent to value based insurance for most of crops and livestock. Different governments programs such as youth self-employment program, youth focused program, spring rice promotion program and other grant/subsidy programs under different mega projects of GoN have started to link agriculture insurance with their programs. Insurance has been made mandatory to get such any subsidy support from the government for promoting agriculture insurance simultaneously. However, this study found that this strategy did not adequately work. But if they feel the enterprises is risky and realize the importance of agriculture insurance and can get higher returns from the enterprises, they were willing to participate in agriculture insurance. Most of farmers who participated in government grant program have limited understanding of crop insurance so that they have discontinued insurance after the end of grant/subsidy program. Therefore, it is necessary to revisit the existing provision of grant linked insurance and need to focus more on creating awareness on importance of agriculture insurance for its sustainability.